2022
DOI: 10.1002/jbm.b.35147
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytocompatibility and antibacterial studies on biodegradable Zn alloys supplemented by a critical assessment of direct contact cytotoxicity assay

Abstract: In vitro cytotoxicity assessment is indispensable in developing new biodegradable implant materials. Zn, which demonstrates an ideal corrosion rate between Mg-and Fe-based alloys, has been reported to have excellent in vivo biocompatibility. Therefore, modifications aimed at improving Zn's mechanical properties should not degrade its biological response. As sufficient strength, ductility and corrosion behavior required of load-bearing implants has been obtained in plastically deformed Zn-3Ag-0.5Mg, the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 109 publications
1
8
0
Order By: Relevance
“…Furthermore, the measurements are in a similar range compared to previous studies on biomaterials [50,51]. W ątroba et al hypothesized that a surface roughness of 0.22 µm is adequate for MG-63 cells [52]. According to Andrukhov et al [53], even a surface roughness of 1-2 µm is suitable for osteoblastic cells.…”
Section: Sample Characterizationsupporting
confidence: 61%
“…Furthermore, the measurements are in a similar range compared to previous studies on biomaterials [50,51]. W ątroba et al hypothesized that a surface roughness of 0.22 µm is adequate for MG-63 cells [52]. According to Andrukhov et al [53], even a surface roughness of 1-2 µm is suitable for osteoblastic cells.…”
Section: Sample Characterizationsupporting
confidence: 61%
“…After that time, this cell culture media containing the degradation products of each sample (conditioned media) were administered to cultured cells (20,000 cells per well) seeded in a 24‐well plate. The cells were kept under incubation with the conditioned media for 24 h. This in‐direct cytotoxicity method was followed as recommended by the ISO 10993‐5: 2009 and widely employed in the literature for cytotoxicity assays 40 . To measure the metabolic activity the samples were submitted to a colorimetric assay.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were kept under incubation with the conditioned media for 24 h. This in-direct cytotoxicity method was followed as recommended by the ISO 10993-5: 2009 and widely employed in the literature for cytotoxicity assays. 40 To measure the metabolic activity the samples were submitted to a colorimetric assay. The samples were treated with CellTiter Blue following the manufacturer protocols.…”
Section: Metabolic Activitymentioning
confidence: 99%
“…% Zn exhibited the best osteogenetic effect. However, some studies have shown that Zn ion at concentration of 13.4 mg l −1 kill 50% of human osteosarcoma (MG-63) cells [34]. It was evident that cells were less tolerant to Zn ions than to Si ions.…”
Section: Cell Behaviors On the Composite Scaffoldsmentioning
confidence: 99%